2001
DOI: 10.1128/mcb.21.5.1819-1827.2001
|View full text |Cite
|
Sign up to set email alerts
|

Two Survivor Pathways That Allow Growth in the Absence of Telomerase Are Generated by Distinct Telomere Recombination Events

Abstract: Yeast cells can survive in the absence of telomerase RNA, TLC1, by recombination-mediated telomere elongation. Two types of survivors, type I and type II, can be distinguished by their characteristic telomere patterns. RAD52 is essential for the generation of both types of survivors. Deletion of both RAD50 and RAD51 produces a phenotype similar to that produced by deletion of RAD52. Here we examined the effects of the RAD50 and the RAD51 epistasis groups as well as the RAD52 homologue, RAD59, on the types of s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
295
2

Year Published

2002
2002
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 252 publications
(307 citation statements)
references
References 29 publications
10
295
2
Order By: Relevance
“…Both rad50 7 tlc1 7 and rad51 7 tlc1 7 strains gave rise to survivors, but a triply mutant rad50 7 rad51 7 tlc1 7 strain was as defective as a rad52 7 tlc1 7 strain at generating post-senescent survivors. These two pathways correlated with the two classes of survivors recovered from S. cerevisiae: type I survivors required RAD51 function whereas type II survivors were dependent on RAD50 function (Teng et al, 2000;Chen et al, 2001). However, the correlation between recombination pathway and survivor class may not be absolute, as type II survivors could form in a rad50 7 mutant background, at least at low frequency, but could not be stably maintained (Chen et al, 2001).…”
Section: A Summary Of Potential Molecular Mechanismsmentioning
confidence: 99%
See 2 more Smart Citations
“…Both rad50 7 tlc1 7 and rad51 7 tlc1 7 strains gave rise to survivors, but a triply mutant rad50 7 rad51 7 tlc1 7 strain was as defective as a rad52 7 tlc1 7 strain at generating post-senescent survivors. These two pathways correlated with the two classes of survivors recovered from S. cerevisiae: type I survivors required RAD51 function whereas type II survivors were dependent on RAD50 function (Teng et al, 2000;Chen et al, 2001). However, the correlation between recombination pathway and survivor class may not be absolute, as type II survivors could form in a rad50 7 mutant background, at least at low frequency, but could not be stably maintained (Chen et al, 2001).…”
Section: A Summary Of Potential Molecular Mechanismsmentioning
confidence: 99%
“…These two pathways correlated with the two classes of survivors recovered from S. cerevisiae: type I survivors required RAD51 function whereas type II survivors were dependent on RAD50 function (Teng et al, 2000;Chen et al, 2001). However, the correlation between recombination pathway and survivor class may not be absolute, as type II survivors could form in a rad50 7 mutant background, at least at low frequency, but could not be stably maintained (Chen et al, 2001). Additional analysis has shown that other members of the RAD51 epistasis group (RAD54, RAD55 and RAD57) were also required for the appearance of type I survivors (Le et al, 1999;Chen et al, 2001).…”
Section: A Summary Of Potential Molecular Mechanismsmentioning
confidence: 99%
See 1 more Smart Citation
“…These survivors can be distinguished into type I and type II based on their telomere structure. Type I survivors have short telomeres that are maintained by recombination in the telomere-associated Y 0 element, while type II survivors have very long and heterogeneous telomeres that are likely maintained by intertelomeric recombination (Teng and Zakian, 1999;Teng et al, 2000;Chen et al, 2001). Human ALT cells are reminiscent of type II survivors in yeast (Lundblad and Blackburn, 1993;Bryan et al, 1995Bryan et al, , 1997aTeng and Zakian, 1999).…”
Section: C3-cl6 Cells Do Not Have Subtelomeric Amplificationmentioning
confidence: 99%
“…Lond. B (2002) of Werner's (WRN) and Bloom's (BLM) syndromes (Huang et al 2001;Chen et al 2001;Le et al 1999).…”
Section: Phil Trans R Soc Lond B (2002)mentioning
confidence: 99%